2019
DOI: 10.1016/j.btre.2019.e00308
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of pigment production through media composition, abiotic and biotic factors in two filamentous fungi

Abstract: HighlightsPigment production and accumulation is dependent of high C:N ratios in F. oxysporum and A. chevaleri.Red pigment content of F. oxysporum in terms of Absorbance units per gram of biomass increased in 191% through use of blue light. Different light wavelengths stimulate synthesis of additional pigments in A. chevalieri with highest accumulation in red and UV-light.Stimulation of pigment production in co-culture is species – specific, being only accomplished in A. chevalieri. With a rise higher that 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 69 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…Accordingly, it has been shown that light increases fumonisin biosynthesis in Fusarium spp. [ 67 ] and that blue light triggers red pigment content of F. oxysporum [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been shown that light increases fumonisin biosynthesis in Fusarium spp. [ 67 ] and that blue light triggers red pigment content of F. oxysporum [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the induction or enhancement in pigment production was possible using co-culturing of fungi with bacteria or yeast, but it was species-specific. In case of Monascus and A. chevalieri, co-culturing was found to be effective, whereas in case of F. oxysporum, the results were negative [158,170]. Co-culturing of C. neoformans with Klebsiella aerogenes led to synthesis of melanin by the fungus, using dopamine synthesized by bacteria [171].…”
Section: Optimization For Enhancement Of Pigment Productionmentioning
confidence: 99%
“…Most of the studies have shown that incubation in total darkness resulted in enhanced biomass and pigment production [152,155,156]. Studies have also reported that there is an enhancement in the pigment production in the case of A. alternata and M. ruber when exposed to blue and red light, respectively [156,157], and in F. oxysporum when exposed to blue and green light [158]. In contrast, reduction in biomass and pigment yield has been observed in I. farinosa, E. nidulans, F. verticillioides, P. purpurogenum (currently known as C. farinosa, A. nidulans, F. fujikuroi, T. purpureogenus, respectively), and M. purpureus when exposed to green and yellow light [155].…”
Section: Optimization For Enhancement Of Pigment Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural pigments come from plants, animals and microorganisms, but few are available in amounts sufficient for commercial use as food and beverage formulations (Palácio-Barrera et al, 2019;Wójciak et al, 2011). The most common natural pigments are obtained from plants, namely carotenoids, chlorophylls, anthocyanins and betalains, but natural dyes can be produced from non-vegetable sources such as animals and microorganisms (Sánchez-Muñoz et al, 2020;Stachowiak, 2014).…”
Section: Introductionmentioning
confidence: 99%